2000
DOI: 10.1086/308973
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of NGC 1068: Probing the Obscured Ionizing AGN Continuum

Abstract: The ISO-SWS 4 infrared spectroscopic observations of the nucleus of Seyfert galaxy NGC 4151, which are described in a companion paper, are used together with a compilation of UV to IR narrow emission line data to determine the spectral shape of the obscured extreme-UV continuum that photoionizes the narrow line emitting gas in the active galactic nucleus. We present a new method to determine the best fitting photoionizing continuum and emission line cloud model from a heterogeneous set of emission line data.Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 105 publications
(132 reference statements)
2
59
0
Order By: Relevance
“…Snow & Witt 1996) : C, 65% ; O, 50% ; Si, Mg, and Fe, 100%. Although Alexander et al (2000) report evidence of the presence of a big blue bump in the SED of the ionizing continuum, in Paper II we demonstrated that the emissionline spectrum from the hot spot could be produced by a simple power-law continuum. Here we assume the same ionizing continuum used in Paper II, speciÐcally a broken power law of the form as follows (also, see…”
Section: Photoionization Modelsmentioning
confidence: 63%
See 2 more Smart Citations
“…Snow & Witt 1996) : C, 65% ; O, 50% ; Si, Mg, and Fe, 100%. Although Alexander et al (2000) report evidence of the presence of a big blue bump in the SED of the ionizing continuum, in Paper II we demonstrated that the emissionline spectrum from the hot spot could be produced by a simple power-law continuum. Here we assume the same ionizing continuum used in Paper II, speciÐcally a broken power law of the form as follows (also, see…”
Section: Photoionization Modelsmentioning
confidence: 63%
“…Notably, if there is mix of optically thin and thick components among the emission-line gas, as is the case in the NE-blue quadrant, the lower value of the He II j4686/Hb ratio is evidence for a paucity of photons above the He II Lyman limit, which can be caused by an intervening absorber (Alexander et al 1999 ;. As mentioned in°1, Alexander et al (2000) found strong evidence that the narrow-line gas in NGC 1068 is irradiated by continuum which has been partially absorbed by a neutral hydrogen column of D6 ] 1019 cm~2. Similar to the situation for NGC 4151 , we modeled the absorber as a large column of highly ionized gas (an "" X-ray ÏÏ absorber) and a thinner, outer layer of low ionization gas (a "" UV ÏÏ absorber).…”
Section: Ne-redshifted Quadrantmentioning
confidence: 90%
See 1 more Smart Citation
“…More speciÐcally, it is overluminous in hard X-rays by about an order of magnitude. Possibly, the dust extinction toward the nucleus of NGC 6240 is much higher than assumed based on NIR colors (Tecza et al 2000 ;Alexander et al 2000). Indeed, NGC 6240 is the most distant object of our sample, and the observations sample larger spatial scales (approximately kiloparsecs).…”
Section: Mirèx-ray Correlationmentioning
confidence: 78%
“…In order to do so, we predicted the line intensities as a function of redshift (in the range z=0.1-5) for three local template objects: NGC1068 (Alexander et al, 2000;Spinoglio et al, 2005), a prototypical Seyfert 2 galaxy containing both an AGN and a starburst; NGC6240 (Lutz et al, 2003), a bright starburst with an obscured AGN and M82 (Forster Schreiber et al, 2001;Colbert et al, 1999), the prototypical starburst galaxy. We assumed that the line luminosities scale as the bolometric luminosity and adopted a luminosity evolution proportional to (z+1) 2 , consistent with recent Spitzer results at least up to redshift z=2 (Perez-Gonzalez et al, 2005 For simplicity 1 , we adopted an Einstein-De Sitter model Universe, with Ω Λ = 0 and Ω M = 1, H 0 =75 km s −1 Mpc −1 .…”
Section: Are Local Templates Observable At High Z ?mentioning
confidence: 99%